Review of Calenda, G. Un Universo Aperto. La cosmologia di Parmenide e la struttura della Terra (2017) (Revista Archai, 2020)
Review of Calenda, G. Un Universo Aperto. La cosmologia di Parmenide e la struttura della Terra (2017)